1999
DOI: 10.1149/1.1392018
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Properties of Electroplated CoNiFe Films

Abstract: Electroplated CoNiFe films with a saturation flux density as high as 2.1 T are potentially useful in high‐density magnetic recording heads. We found that films electroplated at a high current density false(15 normalmA/cm2false) from a bath without saccharin have a sufficient anodic pitting‐corrosion potential (−65 mV). We also found that the pitting‐corrosion potential of films electroplated under a low current density false(5 normalmA/cm2false) from saccharin‐free baths have anodic pitting‐corrosion poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The corrosion rate for the control titanium surface determined from the Tafel plot was found to be 3.1 × 10 −6  mA/cm 2 whereas the corrosion rate for the black titanium was 6.3 × 10 −5  mA/cm 2 (Figure S8). Although the current density observed on the black titanium surface displayed one-fold increase over that of the control, both these values are lower than that of other metallic materials3839. Thus, the black titanium exhibits good corrosion resistance and is well suited for use as a biomaterial.…”
Section: Resultsmentioning
confidence: 83%
“…The corrosion rate for the control titanium surface determined from the Tafel plot was found to be 3.1 × 10 −6  mA/cm 2 whereas the corrosion rate for the black titanium was 6.3 × 10 −5  mA/cm 2 (Figure S8). Although the current density observed on the black titanium surface displayed one-fold increase over that of the control, both these values are lower than that of other metallic materials3839. Thus, the black titanium exhibits good corrosion resistance and is well suited for use as a biomaterial.…”
Section: Resultsmentioning
confidence: 83%
“…9,10 Saito et al investigated electrodeposited CoNiFe and found that pitting potentials shifted to more negative potentials with increasing saccharin concentration. 11 The corrosion behavior was also affected by deposition parameters and can be improved by reducing grain size. 11 Even though there are many studies on electrodeposited irongroup alloys, there is a lack of systematic studies relating properties of electrodeposited iron group thin films including NiFe, CoNi, CoFe, and their ternary alloys with deposit composition, grain size, and crystal structure.…”
mentioning
confidence: 99%
“…At the same time, however, such inclusion might affect the corrosion resistance of the film as observed in CoNiFeS films [11], [12]. Thus, we also investigated the corrosion resistance of CoNiFeC film in a 2.5-wt% NaCl aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it should also be noted that the corrosion resistance of the film is related to its crystallinity. It was reported that the inferior corrosion resistance of amorphous-like CoNiFe film was drastically improved by annealing at 250 C, while that of CoNiFeS film did not and that the annealing led to slight improvement of crystallinity of the former film while defects within the latter film still remained [12]. For the present CoNiFeC film, it was shown from TEM and THEED results, which are omitted here, that the annealing caused an improvement in crystallinity not in grain growth, similar to CoNiFe rather than CoNiFeS.…”
Section: Resultsmentioning
confidence: 99%